(untitled) (Andamios, Revista de Investigación Social, 2010)
This article tries to comprehend the complex relation between politics and mass media in Argentina using as starting point the recently passed law on Audiovisual Communication Services (Law No 26522) on October 10, 2009. In particular, we discuss the relation between Grupo Clarin with the last two Argentinian administrations lead by Néstor Kirchner y Cristina Fernández de Kirchner, respectively. In the context of these relations, media-politics and Kirchner-Clarín, we analyze the impact on the democtratic life in Argentina of both, the continuous federal attempt to impose control over the media and the reciprocal partial news coverage carried out by media.